Efeitos do período de incubação de fosfatos naturais no solo sobre a disponibilidade de fósforo para as plantas - Defelipo, Braz Vitor; de Souza, Jonas; Braga, José Mário; Alvarez Venegas, Victor Hugo (Revista Ceres, 2025)
The objective of this study was to determine the efficiency of four rock phosphates — Patos, Araxá, Catalão e Tapira — as compared to concentrated superphosphate as sources of phosphorus to plants. Four levels of P and three incubation periods were employed. The experiments were carried out under greenhouse conditions using a soil from Irecê, Bahia (an Eutrophic Latosolic Cambisol) and one from Ituiutaba, Minas Gerais (a Dark Red Latosol). Sorghum, Sorghum bicolor (L.) Moench, variety ‘DK-E 57, was used as the test plant.